A comparative evaluation of extraction socket preservation with demineralized freeze-dried bone allograft alone and along with platelet-rich fibrin: A clinical and radiographic study - Dhaval J Thakkar; Neeraj C Deshpande; Deepak H Dave; Suraj D Narayankar (Wolters Kluwer Medknow Publications, 2016)
Aims: To investigate clinically and radiographically, the bone fill in extraction sockets using demineralized freeze-dried bone allograft alone and along with platelet-rich fibrin (PRF). Materials and Methods: A randomized controlled clinical trial was carried out on 36 nonrestorable single-rooted teeth sites. Sites were randomized into demineralized freeze-dried bone allograft (DFDBA) combined with PRF - test and DFDBA - control groups using a coin toss method. After the placement of graft material, collagen membrane was used to cover it. The clinical parameters recorded were ridge width and ridge height. All the parameters were recorded at baseline and at 90 and 180 days. Statistical Analysis Used: Independent t-test and paired t-test. Results: In both groups, there is significant reduction in loss of ridge width and ridge height from baseline to 90 days (P < 0.001), baseline to 180 days (P < 0.001), and 90-180 days (P < 0.001). However, when both the groups were compared the test group favored in the reduction of ridge width while there was no statistical difference in reduction of ridge height among at different intervals. Conclusions: Although DFDBA is considered as an ideal graft material, PRF can be used as an adjunctive with DFDBA for socket preservation.